Penyuluhan Sistem Infomasi Akuntansi Untuk Industri Kerajinan Logam Di Desa Cepogo, Kabupaten Boyolali - Setia Ningsih; Anisa Wantifa Pratiwi; Intan Putri Wijaya; Tutik Alawiyah; Jeckly Nurdiakusuma; Dimas Ilham Nur Rois; Sari Kurniati (Yayasan Kajian Riset dan Pengembangan RADISI, 2021)
Industry 4.0, which is increasingly spreading to various regions in Indonesia, makes people confused. Especially in the metal craftsman community, therefore it is necessary to have an Accounting Information System (SIA) to make it easier for craftsmen to do bookkeeping efficiently. Therefore, there is a need for guidance or socialization in advance to the community how important AIS is in today's era. With the holding of the briefing or socialization, the community becomes motivated in using and developing AIS to improve human resources (HR) by creating behavioral changes.